Development and Validation of Micro-Lecture Videos as Learning Support Material for Grade 7 Science Competencies - De Oca, Phillip Raymund R.; Villaceran, Lyndon G.; Deoma, Mark Enrique B.; Linaugo, Joji D.; Abao, Grace M.; De Oca, Marielle Grace A. (Future Science / FSH-PH Publications, 2024)
As students opted for modular distance learning during the pandemic, they were forced to self-regulated learning with little assistance from teachers. Video lectures are materials commonly designed for active learning methods in distance learning. However, studies found that the length of videos has a strong influence on students’ control over their learning. Longer videos have issues sustaining students’ focused attention to content. This study aimed to develop, validate and evaluate the quality and effectiveness of micro-lecture videos in Physics. Using the developmental research design anchored on the ADDIE model, 7 videos were developed. Videos were quality assured and administered to grade 7 students for evaluation, and feedbacking. Using a developed instrument, an LRMDS standard evaluation tool from the Department of Education, and thematic analysis, quality assurance results, test scores, and interview transcripts were gathered and analyzed statistically and thematically. Results show that despite limited engagement, video lectures are vital so students are guided to self–regulate their learning at their own pace. They also brought positive outcomes, particularly on ownership of learning where students manage and control the pace of their video view, allowing them to replay anytime. On the quality of materials, micro-lecture videos have relevant, logically arranged information, with appropriate content and language that are free of bias. They also have a well-defined purpose, are content-friendly, and can engage viewers for a better understanding of concepts. Moreover, end-users responded that the material was easy to use, can be viewed in messenger, and can be downloaded anytime since it has a smaller file size.